Analysis of three-dimensional computed tomography talar morphology in relation to pediatric pes planovalgus deformity. Issue 6 (November 2019) - Lee, Kyoung Min; Chung, Chin Youb; Park, Moon Seok; Sung, Ki Hyuk; Koo, Seungbum; Moon, Sang Il; Wang, Soon Do; Jung, Ki Jin
Abstract : Intraosseous alignment of the tarsal bone has not been investigated in relation to various foot deformities. This study aimed to investigate three-dimensional computed tomography (3D CT) talar morphology in children with idiopathic and neuromuscular pes planovalgus. Eleven children [nine boys, two girls; mean (SD) age: 10.5 (2.8) years] with idiopathic pes planovalgus and 15 children [three boys, 12 girls; mean (SD) age: 10.8 (3.4) years] with neuromuscular pes planovalgus were included. All patients underwent 3D CT and weight-bearing anteroposterior, lateral, and axial radiography. Demographic data and talar 3D CT and radiographic measurements were compared between both groups. The correlation between the measurements was also analyzed. The neuromuscular group showed significantly more severe deformity than the idiopathic group in the radiographic and 3D sagittal talus measurements. The 3D coronal talus measurement showed a significant negative correlation with the axial hindfoot alignment in the idiopathic group while the 3D transverse talus measurement was significantly correlated with the lateral talocalcaneal angle in the neuromuscular group. 3D intraosseous alignment of the talus is correlated with pes planus deformity. Longitudinal and biomechanical studies including a control group are necessary to elucidate the role of 3D talar morphology on a dynamic imbalance in pes planovalgus.